Formal techniques for distributed objects, components, and systems : 39th IFIP WG 6.1 International Conference, FORTE 2019, held as part of the 14th International Federated Conference on Distributed Computing Techniques, DisCoTec 2019, Kongens Lyngby, Denmark, June 17-21, 2019, Proceedings /: 39th IFIP WG 6.1 International Conference, FORTE 2019, held as part of the 14th International Federated Conference on Distributed Computing Techniques, DisCoTec 2019, Kongens Lyngby, Denmark, June 17-21, 2019, Proceedings. ([2019]) - Unknown
No abstract available